Evaluasi Kegiatan Pemberdayaan Masyarakat Desa dari Dana Desa Mudalrejo Kecamatan Loano Kabupaten Purworejo - R Arif Muhadhib; Anna Probowati; Dewi Shanti Nugrahani (STIE Rajawali Purworejo, 2025)
This study aims to evaluate village community empowerment activities funded by Village Funds in Mudalrejo Village, Loano District, Purworejo Regency. Village Funds allocated by the central government are expected to encourage increased community welfare through empowerment programs that involve active community participation in the planning and implementation process. This evaluation was conducted using a qualitative approach that combines in-depth interview methods, observation, and documentation studies of the implementation of empowerment activities using Village Funds. The focus of this study covers three main aspects, namely: effectiveness of fund use, level of community participation, and socio-economic impacts on village communities. The results of the study indicate that although there are several challenges in implementation, such as lack of understanding of budget management and limited human resource capacity, empowerment activities funded by Mudalrejo Village Funds have had a positive impact on improving people's standard of living, especially in the economic and village infrastructure sectors. The community showed active participation in the activities carried out, although there were several obstacles related to the involvement of marginalized groups. This study recommends the need to increase human resource capacity, transparency in fund management, and improve communication between the village government and the community for the sustainability of empowerment in the future.